How do secondary school students from the Kurdistan Region of Iraq understand the concept of function? - Hussein, Yusuf Fakhraddin; Csíkos, Csaba (Teaching Mathematics and Computer Science, 2022)
The study investigates secondary school students’ understanding of the concept of function. The paper focuses on three main aspects: students’ ability to define the concept of function; students’ ability to recognize different representations of function; and students’ ability to convert between different representations. A test was developed to assess the three main constructs of the study and administered to 342 students in secondary schools in the Kurdistan Region of Iraq. According to the results, students have diffculties in recognizing different representations of function and conversion between them. Connections between different parts of the test may provide hints on educational challenges of how to appropriately teach functions. Subject Classification: 26Bxx, 97D60